Serum complement levels as prognostic marker for monitoring treatment response in lupus nephritis (BIRDEM Medical Journal, 2021)
Background: Lupus nephritis (LN) is one of the most common and serious manifestations of systemic lupus erythematosus (SLE) that causes significant morbidity and mortality. Certain biomarkers for LN are sometimes able to assess treatment response in lupus nephritis. This study aimed to compare serum complement levels (C3 and C4) as markers of treatment response of LN and their relation to the LN class in renal biopsy.Methods: This prospective observational study was conducted in the Department of Nephrology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from July 2018 to August 2019. Twenty seven patients who were diagnosed with LN after kidney biopsy were included in this study. Serum complement levels (C3 and C4), 24 hours urinary total protein (24-hr UTP) and anti-double-stranded DNA (anti-ds DNA) were measured in all patients at baseline, 3 months and 6 months after treatment initiation. These biomarker values before and after treatment were compared between the proliferative and non-proliferative LN patients.Results: Serum C3 levels were significantly different between patients with proliferative LN (Class III and Class IV) and non-proliferative LN (Class V) at baseline (0.47 ± 0.32 g/l versus 0.89 ± 0.43 g/l, p=0.009) and levels changed significantly 6 months after treatment initiation (p